Assessment of the Effect of Graded Doses Alligator Pepper on Uterus of Female Albino Rats - Mathew, Uwuigbe; Ohiwerei Wisdom Omogbai; Amina Momodu; Ogbe O Clementina (MultiTech Publisher, 2024)
The aim of this study is to determine the histological effects of alligator on the uterus of wistar rats, as a result of different doses of alligator administered orally. Fifty (50) adult female wistar rats were use for this study for a period of 28 days (14 days for aclimitization and 14 days for administration). The rats were randomized and divided into five groups (A, B, C, D and E) of ten (10) animals each. the animals were sacrificed two times. All animals were sacrificed by cervical dislocation at least three hours after the last administration of alligator pepper. The results showed the weight before acclimatization, after acclimatization, before sacrifice of control and test subjects in which the Mean±SEM of weight before acclimatization, after acclimatization, before sacrifice were 247±3.00, 226±2.00 and 226±2.00 respectively for control subjects. None of the test groups were found statistically significant (p<0.05) when compared with their respective control. The micrograph result showed that ovary group A in the photomicrograph had a normal histological features. Uterus group B administered with 100mg/kg of aqueous extracts of alligator pepper showed clear carcinoma (neoplastic changes) of the endomentry uterus. Uterus group C (200mg of Alligator pepper) and group D (300mg of Alligator pepper) showed hyperplasic cells of the endomentry uterus. Uterus group E (400g of Alligator pepper) photomicrograph showed andenomyosis endoutrolysis internal. In conclusion, hyperplasic cells ( a condition suggestive of Hyperplasia) was found to be more common in groups with moderate doses. This study suggests that the oral administration of Alligator pepper at mild or moderate doses could cause severe histopathologic changes in the uterus without having any adverse effect on body weight